If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x + 2) = 3x + -4 Reorder the terms: f(2 + x) = 3x + -4 (2 * f + x * f) = 3x + -4 (2f + fx) = 3x + -4 Reorder the terms: 2f + fx = -4 + 3x Solving 2f + fx = -4 + 3x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Reorder the terms: 4 + 2f + fx + -3x = -4 + 3x + 4 + -3x Reorder the terms: 4 + 2f + fx + -3x = -4 + 4 + 3x + -3x Combine like terms: -4 + 4 = 0 4 + 2f + fx + -3x = 0 + 3x + -3x 4 + 2f + fx + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 4 + 2f + fx + -3x = 0 The solution to this equation could not be determined.
| (x-120)*1.8+60=90 | | 1/5x=70 | | 5g-1=3g+4 | | sqrt(17-y)+sqrty(y)=5 | | 3x=5(7) | | 100=x/2*100 | | X=100-(x*15/100) | | 3x+9x-5x= | | -0.12p=2.56+5p | | X=2*10 | | (t)(sqrt(4-t))=0 | | 10n+5=5 | | y=8x^2-6x-14 | | 4-4*5-3= | | -19/5*-4 | | 19/5*-4 | | -19/5*4 | | x^3=212 | | 131/27=x | | 27+x=131 | | x-6(-5/4)=8 | | x-6(5/4)=8 | | 24x+26= | | -2(x-7)-(x+5)=5 | | 12x+x=130 | | r^2-34r+8=0 | | 2J(-5J^3+4J^2-20)-6J^2(-4J^2+3J+7)= | | 0.125x+16=4+0.125 | | 4x^2+30x=4 | | 81/8-6 | | x^2+(12-b)x+b=0 | | 4x^2+6x+0=0 |